OTONOMI PENDIDIKAN ISLAM: TANTANGAN DAN HARAPAN - Hasan Basri; Zuhairansyah Arifin (POTENSIA: Jurnal Kependidikan Islam, 2021)
This article study the problem of Islamic education institutions in Indonesia which is under vertical institution, the Ministry of Religion, but is factually within the scope of an autonomous local government. This problem is studied cccording to management of Islamic education perspective. Educational autonomy is a technical problem in the management of educational institutions which is not necessarily applied equally to all educational institutions, but depends on the condition of educational institutions in each region. Some aspects needed for autonomy is management of student recruitment, utilization and maintenance of facilities and infrastructure, implementation of learning, implementation of evaluation of learning outcomes by teachers, permissibility of community involvement in assisting the administration of education. The general education policies, curriculum and education funds may not be submitted to educational institutions. The government is fully responsible for providing quality education services for all people, also funds and all supporting facilities.